The Analyses on Dynamic and Dedicated Resource Allocation on Xen Server - Mardhani Riasetiawan; Ahmad Ashari; Irwan Endrayanto (Universitas Ahmad Dahlan, 2016)
Data center today challenges is not only serve the users, in same time need to establish scalable resources. Data Center manage the resources such as processor, storage, network, and memory in appropriate way to handle to load. In the big data era, load will increase and come in rapid way with large volume data, many type of data, can be stream and batch data, and unknown sources. Resources need to manage with comprehensive strategies to face the characteristic of big data load. Data Center have capabilties on allocate the reosource in dynamic and dedicated ways. The research investigate in the performance of dedycated and dynamic resource allocation to define the reliable strategies on Data Center. The research work on XenServer platform as Data Center. The research define 18 Virtual Machiens both on dedicated and dynamic strategies, use the shared storage mechanism, and resource pools. The research analyze on CPU performances on XenServer1 and XenServer2 that design as cluster Data Center.The test has run on XenServer and resulting the 2 phase of process when Data Center allocate the resources, there are intiation phase and process phase. The research shown that in the intiation phase both dynamic and dedicated strategies still not running, and use the initial resources to establish Data Center. The process phase shown that dynamic and dedicated strategies run and generating the load process. In the process phase it shown the use of memory and CPU Performance stream line into the balance positions. The research result can use for allocating resources is need to define different strategies in initition and process phase.